(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study investigates the impact of resistance band training on underhand passing skills in 16- 18-year-old male volleyball players at the Bahurekso Kendal Club. Initial observations indicated inadequate underhand passing skills among athletes. A one-group pretest-posttest experimental design was employed, involving 14 male athletes. A pretest using the Brumbach Forearms Pass Wall Volley Test assessed their skills before a 6-week resistance band training program, conducted three times a week. Post-training, a significant improvement was observed, with a Paired Sample t-Test yielding a p-value of 0.000. The average pretest score rose from 28.79 to 49.36, marking a 71.4% improvement. The findings suggest that resistance band training effectively enhances arm muscle strength and body stability, essential for underhand passing. The study recommends integrating this training method into coaching programs and encourages further research on various training techniques for improving volleyball skills.